IMF effect on sporadic-E layers at two northern polar cap sites: Part I – Statistical study - M. Voiculescu; A. T. Aikio; T. Nygrén; J. M. Ruohoniemi (Annales Geophysicae, 2006)
In this paper we investigate the relationship between polar cap sporadic-E layers and the direction of the interplanetary magnetic field (IMF) using a 2-year database from Longyearbyen (75.2 CGM Lat, Svalbard) and Thule (85.4 CGM Lat, Greenland). It is found that the MLT distributions of sporadic-E occurrence are different at the two stations, but both are related to the IMF orientation. This relationship, however, changes from the centre of the polar cap to its border. Layers are more frequent during positive B y at both stations. This effect is particularly strong in the central polar cap at Thule, where a weak effect associated with B z is also observed, with positive B z correlating with a higher occurrence of Es. Close to the polar cap boundary, at Longyearbyen, the B y effect is weaker than at Thule. On the other hand, B z plays there an equally important role as B y , with negative B z correlating with the Es occurrence. Since Es layers can be created by electric fields at high latitudes, a possible explanation for the observations is that the layers are produced by the polar cap electric field controlled by the IMF. Using electric field estimates calculated by means of the statistical APL convection model from IMF observations, we find that the diurnal distributions of sporadic-E occurrence can generally be explained in terms of the electric field mechanism. However, other factors must be considered to explain why more layers occur during positive than during negative B y and why the B z dependence of layer occurrence in the central polar cap is different from that at the polar cap boundary.